Ultrasonographic Assessment of Anatomic Relationship Between the Internal Jugular Vein and the Common Carotid Artery in Infants and Children After ETT or LMA Insertion: A Prospective Observational Study - Du, Yipeng; Wang, Jin; Jin, Limin; Li, Chunping; Ma, Haichun; Dong, Su (Frontiers in Pediatrics, 2020)
Background: There are conflicting results regarding the anatomic relationship between the IJV and the CCA after endotracheal tube (ETT) or LMA insertion in pediatric populations. Aim: To compare the overlap index and anatomic relationship between the IJV and the CCA in infants and children after ETT or LMA insertion by ultrasonography. Method: This single-center, prospective, observational study including 92 infants and children, aged 1 month to 6 years, were grouped according to the airway devices placed: Group ETT(n=44) and Group LMA(n=48). The overlap index and anatomic relationship between the IJV and the CCA before and after airway devices insertion at neutral and 30° head rotation position were evaluated by ultrasonography. Results: In Group ETT, there was no significant difference in the overlap index after intubation in neutral head position or 30° head rotated position on either side. In Group LMA, the overlap indexes were increased significantly after LMA insertion in neutral head position on both sides. The overlap indexes were increased significantly after LMA insertion in 30° head rotated position on both sides. The most common positional relationship between the IJV and the CCA was anterolateral (AL) in both the right side and left side in the neutral head position. In Group ETT, the AL position was still the most common position relationship between the IJV and the CCA before and after intubation in the 30° head rotated position. In Group LMA, anterior (A) position increased significantly after LMA insertion in the left side. In the 30° head rotated position, there was a significant increase to the position after LMA insertion in both the right side and left side. The change from AL to A was increased after LMA insertion, especially in the 30° head rotated position. Conclusions: The overlap indexes of the IJV and the CCA increased significantly in both sides of the neck after LMA placement in neutral head position, especially in 30° head rotated position. The IJVs after LMA placement had tendency to become anterior to the CCA when the head of patient rotated to the opposite direction in infants and children.